Effect of the Fluorination of Graphene Nanoflake on the Dispersion and Mechanical Properties of Polypropylene Nanocomposites - Lee, Min Gyu (Nanomaterials (Basel), 2020)
In order to investigate the effect of fluorination of graphene nanoflake on the dispersibility in polypropylene (PP) composites, fluorinated graphene oxide (FGO) was prepared by solvo-thermal reaction and applied as a filler of the PP nanocomposite. Due to the weakened inter-particle attraction among the graphene nanoflake and reduced surface energy difference between PP and the filler, PP/FGO composites showed better exfoliation and dispersion state of the filler compared with that of PP/graphene oxide (GO) or PP/reduced graphene oxide (RGO) composites. The improved exfoliation and dispersion of graphene nanoflake resulted in a significant reinforcement on the composites. The Young’s modulus and tensile strength of PP composites filled with 2 wt% of FGO increased by 31% and 15%, respectively, compared with those of PP.